Pelatihan Resolusi Konflik pada Ibu Rumah Tangga di Komunitas Suburban - Ariyani, Mira; Tridinata Wijaya, Redo; Simanjuntak, Dewi Fransiska; Suryaratri, Ratna Dyah; Wahyuni, Lussy Dwiutami; Lubis, Syahid Izharuddin (Universitas Negeri Jakarta, 2025)
Conflict resolution is an essential life skill, particularly for mothers living in suburban communities, where social pressures, family responsibilities, and community dynamics can lead to interpersonal challenges. In response, a service team conducted a conflict resolution training program for mothers in these communities. The training was evaluated by assessing its impact on their conflict resolution strategies. A pretest-posttest comparison design was used to measure changes in conflict resolution behavior before and after the training. The evaluation results showed a positive increase from the pretest (M = 8.23, SD = 1.33) to the posttest (M = 8.28, SD = 1.05). Although the improvement was relatively small, it still indicates a potential shift in participants’ perspectives regarding conflict resolution. Since conflict resolution skills require habituation and ongoing support, long-term interventions are more effective than brief sessions that merely raise initial awareness.